Effect of donor length on electronic structures and charge transport polarity for DTDPP-based D–A copolymers: a computational study based on a super-exchange model. Issue 25 (8th June 2018) - He, Feifei; Cheng, Changli; Geng, Hua; Yi, Yuanping; Shuai, Zhigang
Abstract : Based on an SE model, we understand the change of the charge transport polarity of (DTDPP- n T) polymers at a molecular level. Abstract : With the number of thiophene units increasing from 1 to 5 for dithiophenyldiketopyrrolopyrrole-( n -thiophene) (DTDPP- n T) polymers, we found that their band gap increases and their bandwidth narrows from first-principles computations; their transport polarity changes from n-type ( n = 1, 2, 3) to ambipolar ( n = 4) and finally to p-type ( n = 5). The electronic structures and transport polarity can be understood from an intra-chain super-exchange (SE) mechanism. For different donor lengths, the SE model changed from sandwich-type ( n = 1–4) to staggered-type ( n = 5). As for n = 1–4, the charge transport polarity is determined with the relative magnitude of polarized LUMO and HOMO energy differences of the fragment (DTDPP/ n T). In contrast, DTDPP-5T reveals p-type transport polarity due to the staggered-type SE mechanism. In addition, inter-chain coupling and band edge shift also contribute to the conversion of transport polarity.